Acupuncture therapy on postoperative nausea and vomiting in abdominal operation: A Bayesian network meta analysis. Issue 23 (5th June 2020) - Fu, Chengwei; Wu, Tong; Shu, Qing; Song, Aiqun; Jiao, Yang
Abstract: Background: Postoperative nausea and vomiting (PONV) is a common complication after surgery. However, drugs cannot prevent it completely, and acupuncture therapy shows the potential in preventing PONV, yet the best choice hasn't been demonstrated. Objective: This network meta analysis aimed to evaluate the effectiveness of different acupuncture therapies used for preventing PONV in abdominal operation. Methods: Authors searched articles from PubMed/Medline, Cochrane library, Web of Science, Ebsco and Ovid/Embase, and established database from setup time to June 2019. Quality evaluation of included studies was performed with Cochrane risk-of-bias tool (ROB 2.0). Pairwise and network meta analysis were conducted by RevMan and Addis respectively. Results: Twenty studies with 2862 patients were included in this research. Pairwise meta analysis shows that compared with placebo, transcutaneous electric nerve stimulation had lower risk of postoperative nausea (PON) (odds ratio (OR) = 0.42, 95%confidence interval (CI): 0.30–0.60), postoperative vomiting (POV) (OR = 0.53, 95%CI: 0.36–0.78), PONVs (OR = 0.46, 95%CI: 0.31–0.68), and postoperative rescue (POR) (OR = 0.61, 95%CI: 0.41–0.90), Capsicum had lower risk of PON (OR = 0.16, 95%CI: 0.09–0.28), PONVs (OR = 0.23, 95%CI: 0.12–0.45), Acupressure had lower risk of POV (OR = 0.42, 95%CI: 0.25–0.70), POR (OR = 0.42, 95%CI: 0.27–0.64). In network meta analysis, compared with usual care, the probability rank suggested that Acupoint Injection showed lowest risk of PON (OR = 0.02, 95%CI: 0.00–0.11), POV (OR = 0.06, 95%CI: 0.01–0.49), Usual care for PONVs (OR = 0.31, 95%CI: 0.13–0.75), and Capsicum for POR (OR = 0.39, 95%CI: 0.07–2.33). Further study should be carried out to verify this result. Conclusion: Both pairwise and network meta analysis showed acupuncture therapy was superior to placebo and usual care. Different acupuncture therapy regimens may have advantages in different aspects. And compared with POV, PON seems easier to control. Research results may provide guidance for the prevention of PONV. Systematic review registration: PROSPERO CRD42019147556. Abstract : Supplemental Digital Content is available in the text